Detection of VIM-2-, IMP-1- and NDM-1-producing multidrug-resistant Pseudomonas aeruginosa in Malaysia - Liew, Siew Mun; Rajasekaram, Ganeswrei; Puthucheary, Savithri Devi; Chua, Kek Heng (Elsevier, 2018)
Objectives: The increasing incidence of carbapenem-resistant Pseudomonas aeruginosa along with the discovery of novel metallo-β-lactamases (MBLs) is of concern. In this study, the isolation of MBL-producing P. aeruginosa clinical strains in Malaysia was investigated. Methods: A total of 53 P. aeruginosa clinical strains were isolated from different patients in Sultanah Aminah Hospital (Johor Bahru, Malaysia) in 2015. Antimicrobial susceptibility testing was performed, and minimum inhibitory concentrations (MICs) of imipenem and meropenem were determined by Etest. Carbapenem-resistant strains were screened for MBL production by the imipenem–ethylene diamine tetra-acetic acid (IMP-EDTA) double-disk synergy test, MBL imipenem/imipenem-inhibitor (IP/IPI) Etest and PCR. Multilocus sequence typing (MLST) analysis was performed for genotyping of the isolates. Results: Among the 53 clinical strains, 3 (5.7%) were identified as MBL-producers. Multidrug resistance was observed in all three strains, and two were resistant to all of the antimicrobials tested. Sequencing analysis confirmed that the three strains harboured carbapenemase genes (blaIMP-1, blaVIM-2 and blaNDM-1 in one isolate each). These multidrug-resistant strains were identified as sequence type 235 (ST235) and ST308. Conclusions: The blaIMP-1 and blaNDM-1 genes have not previously been reported in Malaysian P. aeruginosa isolates. The emergence of imipenemase 1 (IMP-1)- and New Delhi metallo-β-lactamase 1 (NDM-1)-producing P. aeruginosa in Malaysia maybe travel-associated.